Tungsten-copper composite material surface coating and preparation method thereof
Through multi-layer coating structure design and advanced coating technology, the thermal stress, ablation losses and oxidative erosion problems faced by tungsten copper composites in ultra-high temperature environments are solved, and the high-temperature service performance and reliability of the material are significantly improved.
Patent Information
- Application Number
- CN202510085428.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
Tungsten-copper composite materials face complex thermal stress, ablation losses and oxidative erosion problems in ultra-high temperature environments, resulting in cracks, peeling and rapid oxidation on the surface, significantly reducing the service life and reliability of the material.
The multi-layer coating structure design is adopted, combined with electrophoretic deposition technology, thermal isostatic pressure treatment and atmospheric plasma spraying technology, optimize the interface combination mode and thermal physical characteristics of the bonding layer, transition layer and thermal insulation and anti-ablation layer, and improve the bonding strength, thermal expansion matching and high temperature stability of the coating.
Significantly improve the high-temperature service performance of tungsten-copper composite materials, enhance the resistance to ablation, thermal shock and oxidation, extend the service life of the material and improve reliability.
Smart Images

Figure CN119899995A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-performance composite materials, and in particular relates to a surface coating of a tungsten-copper composite material, and also relates to a preparation method of the surface coating of the tungsten-copper composite material. Background Art
[0002] Tungsten copper composite materials are widely used in aerospace, nuclear industry, electronic devices and other fields due to their excellent properties in high thermal conductivity, high strength and high temperature resistance. However, tungsten copper materials face complex and extreme thermal stress, ablation loss and oxidation erosion problems in ultra-high temperature environments (such as rocket nozzles, throat liners and key engine components). The surface is prone to cracks, peeling and rapid oxidation, which significantly reduces the service life and reliability of the material.
[0003] To address the above problems, the current common method is to coat the surface of the tungsten copper substrate with an anti-ablation coating. However, the traditional anti-ablation coating technology has the following problems: (1) Insufficient bonding between the coating and the substrate: The low chemical activity and complex thermal expansion characteristics of the tungsten copper material cause the coating to easily fall off under thermal shock and mechanical load, limiting its high-temperature service life; (2) Limited ablation resistance of the coating: Existing anti-ablation coatings mostly use a single ceramic material (such as ZrO2 or SiC), which has insufficient oxidation resistance and thermal shock resistance at high temperatures and cannot adapt to complex working conditions; (3) Unstable preparation process: Many coating preparation methods (such as simple thermal spraying or sputtering technology) have poor control over the density of the coating and the matching of the multilayer structure, resulting in uneven coating performance. Summary of the invention
[0004] The first object of the present invention is to provide a method for preparing a surface coating of a tungsten-copper composite material, which can significantly improve the high-temperature service performance of the tungsten-copper composite material, and achieve high bonding strength, thermal expansion matching and high-temperature stability of the overall coating by scientifically optimizing the interface bonding mode and thermophysical properties of the bonding layer, the transition layer and the thermal insulation and ablation resistance layer.
[0005] The second object of the present invention is to provide a surface coating of a tungsten-copper composite material, which is prepared by the above method.
[0006] The first technical solution adopted by the present invention is a method for preparing a surface coating of a tungsten-copper composite material, comprising the following steps:
[0007] Step 1: Using the tungsten-copper composite material as a substrate, polishing the surface of the tungsten-copper substrate;
[0008] Step 2, preparation of the bonding layer, using the electrophoretic deposition (EPD) method to uniformly deposit the charged bonding layer with metal powder Cr / Ti metal particles on the polished substrate surface, and after drying, perform hot isostatic pressing (HIP) treatment on it; Step 3, preparation of the transition layer, using atmospheric plasma spraying to coat MoSi2 on the bonding layer in step 2;
[0009] Step 4: coat the HfB2-SiC-La2O3 material on the MoSi2 transition layer obtained in step 3 by plasma spraying to obtain a heat-insulating and ablation-resistant layer, thereby completing the preparation of the surface coating of the tungsten-copper composite material.
[0010] The present invention is also characterized in that:
[0011] In step 1, the surface of the tungsten copper substrate is polished with sandpaper to a roughness Ra of 0.2 μm to 0.4 μm, and then ultrasonically cleaned for 20 min to 40 min to remove oxides and oil stains.
[0012] In step 2, the bonding layer is a Cr powder layer or a Ti powder layer or a composite layer of a Cr powder layer and a Ti powder layer; the Cr powder or Ti powder used, step 2 specifically comprises: adding deionized water or ethanol into a container, adding Cr powder or Ti powder according to a powder mass concentration of 30 g / L to 50 g / L, using polyvinyl pyrrolidone as a dispersant, the amount of polyvinyl pyrrolidone relative to the Cr powder or Ti powder is 1 g / L to 2 g / L, stirring evenly, and then using ultrasonic treatment, the ultrasonic frequency is 40 kHz to 60 kHz, and the time is 10 min to 15 min, Prepare a Cr or Ti suspension; place the tungsten-copper composite material with a polished surface in step 1 into an electrolytic cell containing the suspension for electrophoretic deposition, wherein the deposition voltage is 30V to 50V; the electrophoresis time is 2min to 10min; the suspension temperature is 20°C to 25°C; the stirring rate is 200rpm to 400rpm; after the deposition is completed, dry it at 100°C to 150°C for 1 hour, and after it is fully dried, keep it at 900°C to 1000°C for 3h to 5h, perform HIP treatment on the Cr or Ti bonding layer, and complete the preparation of the bonding layer.
[0013] In step 3, the transition layer is prepared by atmospheric plasma spraying, and the specific process parameters are: MoSi2 powder particle size: 15μm~45μm; purity: ≥99%; flow rate of main gas Ar: 35L / min~45L / min; flow rate of auxiliary gas H2: 5L / min~8L / min; arc power is 25kW~40kW; current: 400A~600A; voltage: 50V~70V; spraying distance: 80mm~120mm; spraying rate: 4g / min~6g / min; substrate preheating temperature: 200℃~300℃; coating thickness control: single spraying thickness is 10μm~20μm, and it is superimposed layer by layer to the target thickness: 50μm~150μm.
[0014] Step 4 is specifically as follows: weigh high-purity powders according to the following mass percentages of each component: HfB2 60-80%, SiC 10-30%, La2O3 5-15%, and the powder particle size is 20μm-50μm, put the three powders into a planetary ball mill, use anhydrous ethanol as a solvent, add polyvinyl alcohol equivalent to 0.5%-2% of the total mass of the HfB2-SiC-La2O3 mixed powder as a binder, add silane coupling agent equivalent to 0.1%-1% of the total mass of the HfB2-SiC-La2O3 mixed powder as a dispersant, mix on a planetary ball mill for 8h-12h, and after mixing evenly, prepare spherical HfB2-SiC-La2O3 powder by spray granulation, and directly deposit it on the overcoat by plasma spraying. On the transition layer, the flow rate of the main spraying gas Ar is 35L / min~45L / min; the flow rate of the auxiliary gas H2 is 8L / min~12L / min, the arc power is 35kW~50kW, the current is 400A~600A, the voltage is 50V~70V, the spraying distance is 100mm~150mm, the spraying rate is 15g / min~20g / min; the substrate preheating temperature is 300℃~500℃; the coating thickness control: the single spraying thickness is 10μm~20μm, and it is superimposed layer by layer to the target thickness: 100μm~500μm, and the preparation is completed.
[0015] In step 4, the particle sizes of the three powders of HfB2, SiC and La2O3 are all 20μm to 50μm; in step 4, the ball-to-material ratio is 2:1.
[0016] The second technical solution adopted by the present invention is:
[0017] The surface coating of the tungsten-copper composite material comprises a bonding layer, a transition layer and a heat-insulating and ablation-resistant layer which are sequentially arranged on the surface of a tungsten-copper substrate using the tungsten-copper composite material. The surface coating of the tungsten-copper composite material is prepared by the above method.
[0018] The beneficial effects of the present invention are:
[0019] The principle of the method of the present invention is based on the design of a multi-layer coating structure and the combination of electrophoretic deposition technology, hot isostatic pressing (HIP), and atmospheric plasma spraying (APS) technology to significantly improve the high-temperature service performance of tungsten-copper composite materials. By scientifically optimizing the interface bonding mode and thermophysical properties of the bonding layer, transition layer, and thermal insulation and ablation-resistant layer, the high bonding strength, thermal expansion matching, and high-temperature stability of the overall coating are achieved. The bonding layer (Cr or Ti) forms a diffusion bonding zone with the substrate through electrophoretic deposition technology, and the high temperature and high pressure of the HIP treatment promotes the diffusion and chemical reaction of metal atoms (such as the formation of Cr-Cu or Ti-Cu compounds), which significantly improves the bonding strength and interface density between the coating and the substrate. The transition layer uses MoSi2, and forms a transition structure with the bonding layer and the thermal insulation and ablation-resistant layer through APS thermal spraying. Its thermal expansion coefficient is between the substrate and the thermal insulation layer, which alleviates the thermal stress concentration between the layers of the coating and avoids crack propagation and interface failure. At the same time, under high temperature conditions, MoSi2 undergoes an interfacial reaction with HfB2 and SiC particles to form an interface compound layer of HfSi2 and borosilicide, which enhances the bonding strength of the coating. The thermal insulation and anti-ablation layer is mainly composed of HfB2-SiC-La2O3 and is prepared by APS technology. HfB2 and SiC have excellent antioxidant and anti-ablation properties at high temperatures, generating stable HfO2 and SiO2 protective films; La2O3 further optimizes the microstructure of the coating, improving thermal shock resistance and chemical stability. The coating system is reasonably designed to repair internal pores, enhance interface bonding, reduce interface stress, and improve the ablation resistance, thermal shock resistance, and oxidation resistance of tungsten-copper composite materials, providing an innovative solution for the reliable service of high-temperature equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic diagram of the structure of the surface coating of the tungsten-copper composite material prepared by the method of the present invention;
[0021] Figure 2 SEM photograph of the HfB2-SiC-La2O3 thermal insulation and anti-ablation layer prepared in Example 3.
[0022] In the figure, 1. tungsten copper substrate, 2. bonding layer, 3. transition layer, 4. thermal insulation and anti-ablation layer. DETAILED DESCRIPTION
[0023] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0024] The present invention provides a method for preparing a surface coating of a tungsten-copper composite material, comprising the following steps:
[0025] Step 1: Using the tungsten-copper composite material as a substrate, polishing the surface of the tungsten-copper substrate 1;
[0026] In step 1, the surface of the tungsten copper substrate 1 is polished with sandpaper to a roughness Ra of 0.2 μm to 0.4 μm, and then ultrasonically cleaned for 20 min to 40 min to remove oxides and oil stains.
[0027] Step 2, preparation of the bonding layer 2, using an electrophoretic deposition (EPD) method to uniformly deposit a charged bonding layer of metal powder on the polished substrate surface, and after drying, perform a hot isostatic pressing (HIP) treatment on it;
[0028] In step 2, the bonding layer 2 is a Cr powder layer or a Ti powder layer or a composite layer of a Cr powder layer and a Ti powder layer; the Cr powder or Ti powder used has a particle size of 2 μm to 10 μm and a purity of ≥99.5%;
[0029] Step 2 is specifically as follows: adding deionized water or ethanol to a container, adding Cr powder or Ti powder according to a powder mass concentration of 30 g / L to 50 g / L, using polyvinyl pyrrolidone (PVP) as a dispersant, and the amount of polyvinyl pyrrolidone relative to Cr powder or Ti powder is 1 g / L to 2 g / L, stirring evenly, using ultrasonic treatment, the ultrasonic frequency is 40 kHz to 60 kHz, and the time is 10 min to 15 min to ensure that the Cr powder or Ti powder is fully dispersed and no agglomeration occurs, and a Cr or Ti suspension is prepared; the tungsten-copper composite material after surface polishing in step 1 is placed in an electrolytic cell containing a suspension for electrophoretic deposition, wherein the deposition voltage is 30 V to 50 V; the electrophoresis time is 2 min to 10 min; the suspension temperature is room temperature (20 ° C to 25 ° C); the stirring rate is 200 rpm to 400 rpm to keep the suspension slowly stirred during the deposition process to prevent powder sedimentation. After the deposition is completed, the Cr or Ti bonding layer is dried at 100°C to 150°C for 1 hour. After it is fully dried, it is kept at 900°C to 1000°C for 3h to 5h, and a HIP treatment is performed on the Cr or Ti bonding layer to complete the preparation of the bonding layer.
[0030] Step 3, preparation of transition layer 3: coating MoSi2 on the bonding layer (Cr / Ti) in step 2 by atmospheric plasma spraying;
[0031] In step 3, the transition layer is prepared by atmospheric plasma spraying, and the specific process parameters are: MoSi2 powder particle size: 15μm~45μm; purity: ≥99%; main gas Ar flow rate: 35L / min~45L / min; auxiliary gas H2 flow rate: 5L / min~8L / min; arc power is 25kW~40kW; current: 400A~600A; voltage: 50V~70V; spraying distance: 80mm~120mm; spraying rate: 4g / min~6g / min; substrate preheating temperature: 200℃~300℃; coating thickness control: single spraying thickness 10μm~20μm, layer by layer superimposed to the target thickness: 50μm~150μm, to complete the transition layer preparation.
[0032] Step 4: coat the HfB2-SiC-La2O3 material on the MoSi2 transition layer obtained in step 3 by plasma spraying to obtain a heat-insulating and ablation-resistant layer 4, thereby completing the preparation of the surface coating of the tungsten-copper composite material.
[0033] Step 4 is specifically as follows: weigh high-purity powders according to the following mass percentages of each component: HfB2 60-80%, SiC 10-30%, La2O3 5-15%, put the three powders into a planetary ball mill with a ball-to-material ratio of 2:1 (mass ratio), use anhydrous ethanol as a solvent, add polyvinyl alcohol equivalent to 0.5%-2% of the total mass of the HfB2-SiC-La2O3 mixed powder as a binder, add a silane coupling agent equivalent to 0.1%-1% of the total mass of the HfB2-SiC-La2O3 mixed powder as a dispersant, mix on a planetary ball mill for 8h-12h, and after mixing evenly, prepare spherical HfB2-SiC-La2O3 powder by spray granulation, and directly deposit it on the transition layer by plasma spraying. The flow rate of the main spraying gas Ar is 35L / min~45L / min; the flow rate of the auxiliary gas H2 is 8L / min~12L / min, the arc power is 35kW~50kW, the current is 400A~600A, the voltage is 50V~70V, the spraying distance is 100mm~150mm, the spraying rate is 15g / min~20g / min; the substrate preheating temperature is 300℃~500℃; the coating thickness control: the single spraying thickness is 10μm~20μm, and it is superimposed layer by layer to the target thickness: 100μm~500μm, and the preparation is completed.
[0034] The present invention also provides a surface coating of a tungsten-copper composite material, such as Figure 1 As shown, the tungsten-copper composite material is sequentially arranged as a bonding layer 2, a transition layer 3 and a heat-insulating and ablation-resistant layer 4 on the surface of a tungsten-copper substrate 1, and the surface coating of the tungsten-copper composite material is prepared by the above method:
[0035] (1) Bonding layer 2: Ti and Cr metal powders are bonded to the tungsten copper substrate 1 under high temperature and high pressure by electrophoretic deposition (EPD) and hot isostatic pressing (HIP) technology to form a bonding layer 2 with high bonding strength.
[0036] (2) Transition layer 3: prepared using MoSi2 material through gradient thermal spraying technology to improve the overall thermal expansion matching and mechanical bonding of the coating.
[0037] (3) Thermal insulation and ablation-resistant layer 4: With HfB2-SiC-La2O3 as the core material, it is prepared by hot pressing sintering or plasma spraying, which significantly improves the high-temperature ablation-resistant performance and thermal insulation ability of the coating.
[0038] The surface coating of the present invention is an anti-ablation coating. In this system, Cr and Ti are used as bonding layer materials to form a strong interface bond with the tungsten copper substrate through multiple mechanisms of chemical bonding, diffusion bonding and mechanical bonding. During the spraying process, MoSi2 forms a Cr-Si and Cr-Mo compound interface layer with Cr through diffusion, which improves the bonding strength of the bonding layer and the transition layer. Under high temperature conditions, MoSi2 reacts with HfB2 and SiC particles to form an HfSi2 and boronized silicon interface compound layer, which enhances the interface bonding strength. At the same time, the thermal expansion coefficient of MoSi2 (8.5×10 -6 K -1 ) and HfB2-SiC-La2O3(7.8×10 -6 K -1 ) composite materials, reduce interface thermal stress, and prevent coating peeling and failure while improving the anti-ablation performance of tungsten-copper composite materials during service.
[0039] In the surface coating of the tungsten-copper composite material, the thickness of the bonding layer is 30-50 μm; the thickness of the transition layer is 50-150 μm; and the thickness of the thermal insulation ablation layer is 100-500 μm.
[0040] In the above-mentioned tungsten-copper composite material surface coating, the bonding layer is Cr / Ti; the oxygen transition layer material is MoSi2; in the HfB2-SiC-La2O3 thermal insulation ablation layer, the HfB2 content is 60-80%; the SiC content is 10-30%; and the La2O3 content is 5-15%.
[0041] Example 1
[0042] Step 1: Use sandpaper to polish the surface of the tungsten copper substrate to a roughness of Ra 0.3μm, and then clean it in ultrasonic for 30 minutes to remove oxides and oil stains.
[0043] Step 2, preparation of the bonding layer, using an electrophoretic deposition method to uniformly deposit charged Cr metal particles on the polished substrate surface, and after drying, performing a hot isostatic pressing (HIP) treatment on it;
[0044] The particle size of the Cr powder used is 5 μm, and the purity is ≥99.5%; deionized water is added to the container, and Cr powder is added according to the powder mass concentration of 50 g / L, and polyvinyl pyrrolidone (PVP) is used as a dispersant, and the amount of polyvinyl pyrrolidone relative to the Cr powder is 1.5 g / L. After stirring evenly, ultrasonic treatment is used, and the ultrasonic frequency is 50 kHz, and the time is 10 minutes to ensure that the Cr powder is fully dispersed and does not agglomerate, and a Cr suspension is prepared; the tungsten copper composite material after surface polishing in step 1 is placed in an electrolytic cell containing the suspension for electrophoretic deposition, wherein the deposition voltage is 45 V; the electrophoresis time is 10 minutes; the suspension temperature is 20 ° C; the stirring rate is to keep the suspension slowly stirred during the deposition process, which is 300 rpm to prevent powder sedimentation. After the deposition is completed, it is dried at 120 ° C for 1 hour, and after it is fully dried, it is kept at 950 ° C for 3 hours, and then the Cr bonding layer is HIP treated to form a Cr bonding layer with a thickness of 40 μm.
[0045] Step 3, preparation of transition layer: coating MoSi2 on the bonding layer by atmospheric plasma spraying;
[0046] The transition layer was prepared by atmospheric plasma spraying, and the specific process parameters were: MoSi2 powder particle size: 20μm; purity: ≥99%; flow rate of main gas Ar: 45L / min; flow rate of auxiliary gas H2: 8L / min; arc power: 40kW; current: 600A; voltage: 60V; spraying distance: 120mm; spraying rate: 6g / min; substrate preheating temperature: 300℃; coating thickness control: single spraying thickness 15μm, layer by layer superimposed to the target thickness of 150μm, to complete the transition layer preparation.
[0047] Step 4: The HfB2-SiC-La2O3 material is coated on the MoSi2 transition layer obtained in step 3 by plasma spraying to obtain a heat-insulating and ablation-resistant layer, thereby completing the preparation of the surface coating of the tungsten-copper composite material.
[0048] High-purity powders were weighed according to the following mass percentages of each component: HfB2 70%, SiC 20%, and La2O3 10%. The three powders were placed in a planetary ball mill with a ball-to-material ratio of 2:1 (mass ratio). Anhydrous ethanol was used as a solvent, and polyvinyl alcohol equivalent to 1.0% of the total mass of the HfB2-SiC-La2O3 mixed powder was added as a binder. A silane coupling agent equivalent to 0.5% of the total mass of the HfB2-SiC-La2O3 mixed powder was added as a dispersant. The mixture was mixed on a planetary ball mill for 12 h. After the mixture was evenly mixed, spherical HfB2-SiC-La2O3 was prepared by spray granulation. iC-La2O3 powder is directly deposited on the transition layer by plasma spraying, wherein the flow rate of the main spraying gas Ar is 45L / min; the flow rate of the auxiliary gas H2 is 12L / min, the arc power is 50kW, the current is 500A, the voltage is 60V, the spraying distance is 150mm, and the spraying rate is 20g / min; the substrate preheating temperature is 450℃; the coating thickness control is: the single spraying thickness is 20μm, and the layer is superimposed layer by layer to the target thickness of 450μm to complete the preparation.
[0049] Example 2
[0050] The bonding layer was changed to Ti, and the other steps and parameters were the same as those in Example 1. The coating system finally obtained exhibited excellent thermal expansion matching and high-temperature ablation resistance.
[0051] Example 3
[0052] The bonding layer is a Cr / Ti composite layer, which is deposited by step-by-step electrophoresis: Cr (20 μm) is deposited first, then Ti (20 μm) is deposited, and a 40 μm bonding layer is formed after HIP treatment. The other process steps are the same as in Example 1.
[0053] Figure 2 SEM photo of the HfB2-SiC-La2O3 thermal insulation and ablation resistance layer prepared for Example 3. Figure 2 It can be seen that the surface of the anti-ablation coating is dense and the spraying is uniform. The white one is hafnium compound, which is evenly distributed in the coating, improving the high temperature stability of the tungsten copper material.
[0054] Example 4
[0055] The heat-insulating and ablation-resistant layer material is adjusted to HfB2:SiC:La2O3=60:30:10. The other steps are the same as in Example 1. This formula shows higher thermal shock stability in high-temperature anti-oxidation and anti-ablation performance tests.
[0056] Comparative Example 1
[0057] A single-layer ZrO2 coating was prepared by thermal spraying technology with a thickness of 500 μm. Tests showed that the coating cracked severely in a high-temperature environment and had poor ablation resistance.
[0058] Comparative Example 2
[0059] The transition layer was removed and only the Cr bonding layer and the HfB2-SiC-La2O3 thermal insulation and anti-ablation layer were used. The results showed that the interface bonding strength was low, the coating was easy to peel off, and the performance was significantly reduced.
[0060] The tungsten copper materials with different anti-ablation coatings on the surface prepared in the above examples and comparative examples were placed in a high-temperature air flow environment of 2200°C for 300 seconds to test the performance of the coatings in different examples. As shown in the following table:
[0061]
[0062] The reason for the excellent performance of Example 3 is that it adopts the optimized design of the Cr / Ti composite bonding layer. The Cr layer provides good initial interface bonding force, the Ti layer further improves the thermal expansion matching, and the HIP treatment forms a dense interface bonding with a bonding strength of 50MPa. The MoSi2 of the transition layer buffers the thermal expansion mismatch, and the ratio design of the thermal insulation and ablation resistance layer (HfB2:SiC:La2O3) enhances the compactness and thermal shock resistance of the anti-oxidation protective film, so that the coating as a whole exhibits excellent antioxidant performance (0.4mg / cm 2 ), the lowest ablation rate (0.014mm / h) and the highest interface stability.
[0063] Example 5
[0064] Step 1: Using the tungsten-copper composite material as a substrate, polishing the surface of the tungsten-copper substrate;
[0065] In step 1, the surface of the tungsten copper substrate is polished with sandpaper to a roughness of Ra 0.4 μm, and then ultrasonically cleaned for 40 min to remove oxides and oil stains.
[0066] Step 2, preparation of the bonding layer, using the electrophoretic deposition (EPD) method to uniformly deposit the charged bonding layer with metal powder on the polished substrate surface, and after drying, perform hot isostatic pressing (HIP) treatment on it;
[0067] In step 2, the bonding layer is a Cr powder layer with a particle size of 10 μm and a purity of ≥ 99.5%;
[0068] Step 2 is specifically as follows: add deionized water to the container, add Cr powder according to the powder mass concentration of 50g / L, use polyvinyl pyrrolidone (PVP) as a dispersant, and the amount of polyvinyl pyrrolidone relative to Cr powder is 2g / L. After stirring evenly, use ultrasonic treatment with an ultrasonic frequency of 60kHz and a time of 15min to ensure that the Cr powder or Ti powder is fully dispersed and does not agglomerate, and prepare a Cr or Ti suspension; put the tungsten copper composite material after surface polishing in step 1 into an electrolytic cell containing the suspension for electrophoretic deposition, wherein the deposition voltage is 50V; the electrophoresis time is 10min; the suspension temperature is 25℃; the stirring rate is to keep the suspension slowly stirred during the deposition process, which is 400rpm to prevent powder sedimentation. After the deposition is completed, dry it at 150℃ for 1 hour, and after it is fully dried, keep it at 1000℃ for 5h, and then perform HIP treatment on the Cr or Ti bonding layer to complete the bonding layer preparation.
[0069] Step 3, preparation of transition layer: coating MoSi2 on the bonding layer in step 2 by atmospheric plasma spraying;
[0070] In step 3, the transition layer is prepared by atmospheric plasma spraying, and the specific process parameters are: MoSi2 powder particle size: 45μm; purity: ≥99%; main gas Ar flow rate: 45L / min; auxiliary gas H2 flow rate: 8L / min; arc power is 40kW; current: 600A; voltage: 70V; spraying distance: 120mm; spraying rate: 6g / min; substrate preheating temperature: 300℃; coating thickness control: single spraying thickness 20μm, layer by layer superimposed to the target thickness: 150μm, to complete the transition layer preparation.
[0071] Step 4: coat the HfB2-SiC-La2O3 material on the MoSi2 transition layer obtained in step 3 by plasma spraying to obtain a heat-insulating and ablation-resistant layer, thereby completing the preparation of the surface coating of the tungsten-copper composite material.
[0072] Step 4 is specifically as follows: weigh high-purity powders according to the following mass percentages of each component: HfB2 70%, SiC 20%, La2O3 10%, put the three powders into a planetary ball mill, the ball-to-material ratio is 2:1 (mass ratio), use anhydrous ethanol as a solvent, add polyvinyl alcohol equivalent to 2% of the total mass of the HfB2-SiC-La2O3 mixed powder as a binder, add a silane coupling agent equivalent to 1% of the total mass of the HfB2-SiC-La2O3 mixed powder as a dispersant, mix on a planetary ball mill for 12 hours, and after mixing evenly, prepare spherical HfB2-SiC- La2O3 powder is directly deposited on the transition layer by plasma spraying, wherein the flow rate of the main spraying gas Ar is 45L / min; the flow rate of the auxiliary gas H2 is 12L / min, the arc power is 50kW, the current is 600A, the voltage is 70V, the spraying distance is 150mm, the spraying rate is 20g / min; the substrate preheating temperature is 500℃; the coating thickness control is: single spraying thickness is 20μm, and layer by layer is superimposed to the target thickness: 500μm, and the preparation is completed.
[0073] Example 6
[0074] Step 1: Using the tungsten-copper composite material as a substrate, polishing the surface of the tungsten-copper substrate;
[0075] In step 1, the surface of the tungsten copper substrate is polished with sandpaper to a roughness of Ra 0.2 μm, and then ultrasonically cleaned for 20 min to remove oxides and oil stains.
[0076] Step 2, preparation of the bonding layer, using the electrophoretic deposition (EPD) method to uniformly deposit the charged bonding layer with metal powder on the polished substrate surface, and after drying, perform hot isostatic pressing (HIP) treatment on it;
[0077] In step 2, the bonding layer is a Ti powder layer; the Ti powder used has a particle size of 2 μm and a purity of ≥ 99.5%;
[0078] Step 2 is specifically as follows: add ethanol to the container, add Ti powder according to the powder mass concentration of 30g / L, use polyvinyl pyrrolidone (PVP) as a dispersant, and the amount of polyvinyl pyrrolidone relative to Ti powder is 1g / L. After stirring evenly, use ultrasonic treatment with an ultrasonic frequency of 40kHz and a time of 10min to ensure that the Ti powder is fully dispersed and does not agglomerate, and prepare a Ti suspension; put the tungsten-copper composite material after surface polishing in step 1 into an electrolytic cell containing the suspension for electrophoretic deposition, wherein the deposition voltage is 30V; the electrophoresis time is 2min; the suspension temperature is 20℃; the stirring rate is to keep the suspension slowly stirred during the deposition process, which is 200rpm to prevent powder sedimentation. After the deposition is completed, dry it at 100℃ for 1 hour, and after it is fully dried, keep it at 900℃ for 4h, and then perform HIP treatment on the Ti bonding layer to complete the bonding layer preparation.
[0079] Step 3, preparation of transition layer: coating MoSi2 on the bonding layer in step 2 by atmospheric plasma spraying;
[0080] In step 3, the transition layer is prepared by atmospheric plasma spraying, and the specific process parameters are: MoSi2 powder particle size: 15μm; purity: ≥99%; main gas Ar flow rate: 35L / min; auxiliary gas H2 flow rate: 5L / min; arc power is 25kW; current: 400A; voltage: 50V~70V; spraying distance: 80mm; spraying rate: 4g / min; substrate preheating temperature: 200℃; coating thickness control: single spraying thickness is 10μm, and layer by layer is superimposed to the target thickness: 50μm, and the transition layer preparation is completed.
[0081] Step 4: coat the HfB2-SiC-La2O3 material on the MoSi2 transition layer obtained in step 3 by plasma spraying to obtain a heat-insulating and ablation-resistant layer, thereby completing the preparation of the surface coating of the tungsten-copper composite material.
[0082] Step 4 is specifically as follows: weigh high-purity powders according to the following mass percentages of each component: HfB2 60%, SiC 25%, La2O3 15%, put the three powders into a planetary ball mill, the ball-to-material ratio is 2:1 (mass ratio), use anhydrous ethanol as a solvent, add polyvinyl alcohol equivalent to 0.5% of the total mass of the HfB2-SiC-La2O3 mixed powder as a binder, add a silane coupling agent equivalent to 0.1% of the total mass of the HfB2-SiC-La2O3 mixed powder as a dispersant, mix on a planetary ball mill for 8 hours, and after mixing evenly, prepare spherical HfB2-SiC by spray granulation. -La2O3 powder is directly deposited on the transition layer by plasma spraying, wherein the flow rate of the main spraying gas Ar is 35L / min; the flow rate of the auxiliary gas H2 is 8L / min, the arc power is 35kW, the current is 400A, the voltage is 50V, the spraying distance is 100mm, the spraying rate is 15g / min; the substrate preheating temperature is 300℃; the coating thickness control is: single spraying thickness is 10μm, and layer by layer is superimposed to the target thickness: 100μm, and the preparation is completed.
[0083] Example 7
[0084] Step 1: Using the tungsten-copper composite material as a substrate, polishing the surface of the tungsten-copper substrate;
[0085] In step 1, the surface of the tungsten copper substrate is polished with sandpaper to a roughness of Ra 0.3 μm, and then ultrasonically cleaned for 30 minutes to remove oxides and oil stains.
[0086] Step 2, preparation of the bonding layer, using the electrophoretic deposition (EPD) method to uniformly deposit the charged bonding layer with metal powder on the polished substrate surface, and after drying, perform hot isostatic pressing (HIP) treatment on it;
[0087] In step 2, the bonding layer is a Cr powder layer; the Cr powder used has a particle size of 5 μm and a purity of ≥ 99.5%;
[0088] Step 2 is specifically as follows: add ethanol to the container, add Cr powder according to the powder mass concentration of 40g / L, use polyvinyl pyrrolidone (PVP) as a dispersant, and the amount of polyvinyl pyrrolidone relative to Cr powder is 1.5g / L. After stirring evenly, use ultrasonic treatment with an ultrasonic frequency of 50kHz and a time of 12min to ensure that the Cr powder or Ti powder is fully dispersed and does not agglomerate, and prepare a Cr or Ti suspension; put the tungsten copper composite material after surface polishing in step 1 into an electrolytic cell containing the suspension for electrophoretic deposition, wherein the deposition voltage is 45V; the electrophoresis time is 8min; the suspension temperature is 22°C; the stirring rate is to keep the suspension slowly stirred during the deposition process, which is 300rpm to prevent powder sedimentation. After the deposition is completed, dry it at 110°C for 1 hour, and after it is fully dried, keep it at 950°C for 5h, and then perform HIP treatment on the Cr or Ti bonding layer to complete the bonding layer preparation.
[0089] Step 3, preparation of transition layer: coating MoSi2 on the bonding layer in step 2 by atmospheric plasma spraying;
[0090] In step 3, the transition layer is prepared by atmospheric plasma spraying, and the specific process parameters are: MoSi2 powder particle size: 30μm; purity: ≥99%; main gas Ar flow rate: 39L / min; auxiliary gas H2 flow rate: 7L / min; arc power is 35kW; current: 500A; voltage: 60V; spraying distance: 90mm; spraying rate: 5g / min; substrate preheating temperature: 260℃; coating thickness control: single spraying thickness is 15μm, and layer by layer is superimposed to the target thickness: 100μm, completing the transition layer preparation.
[0091] Step 4: coat the HfB2-SiC-La2O3 material on the MoSi2 transition layer obtained in step 3 by plasma spraying to obtain a heat-insulating and ablation-resistant layer, thereby completing the preparation of the surface coating of the tungsten-copper composite material.
[0092] Step 4 is specifically as follows: weigh high-purity powders according to the following mass percentages of each component: HfB2 75%, SiC 20%, La2O3 5%, put the three powders into a planetary ball mill, the ball-to-material ratio is 2:1 (mass ratio), use anhydrous ethanol as a solvent, add polyvinyl alcohol equivalent to 1% of the total mass of the HfB2-SiC-La2O3 mixed powder as a binder, add a silane coupling agent equivalent to 0.5% of the total mass of the HfB2-SiC-La2O3 mixed powder as a dispersant, mix on a planetary ball mill for 9 hours, and after mixing evenly, prepare spherical HfB2-SiC- La2O3 powder is directly deposited on the transition layer by plasma spraying, wherein the flow rate of the main spraying gas Ar is 40L / min; the flow rate of the auxiliary gas H2 is 9L / min, the arc power is 40kW, the current is 500A, the voltage is 60V, the spraying distance is 110mm, and the spraying rate is 16g / min; the substrate preheating temperature is 400℃; the coating thickness control is: single spraying thickness is 15μm, and layer by layer is superimposed to the target thickness: 400μm, and the preparation is completed.
Claims
1. A method for preparing a surface coating of a tungsten-copper composite material, characterized in that: The following steps are involved: Step 1: Using the tungsten-copper composite material as a substrate, polishing the surface of the tungsten-copper substrate; Step 2, preparation of the bonding layer, using the electrophoretic deposition method to uniformly deposit the charged bonding layer with metal powder on the polished substrate surface, and after drying, hot isostatic pressing is performed on it; Step 3, preparation of the transition layer, coating MoSi2 on the bonding layer in step 2 by atmospheric plasma spraying; Step 4: coat the HfB2-SiC-La2O3 material on the MoSi2 transition layer obtained in step 3 by plasma spraying to obtain a heat-insulating and ablation-resistant layer, thereby completing the preparation of the surface coating of the tungsten-copper composite material.
2. The method for preparing the surface coating of the tungsten-copper composite material according to claim 1, characterized in that: In step 1, the surface of the tungsten copper substrate is polished with sandpaper to a roughness of Ra 0.2 μm to 0.4 μm, and then ultrasonically cleaned for 20 min to 40 min to remove oxides and oil stains.
3. The method for preparing the surface coating of the tungsten-copper composite material according to claim 1, characterized in that: In step 2, the bonding layer is a Cr powder layer or a Ti powder layer or a composite layer of a Cr powder layer and a Ti powder layer; the Cr powder or Ti powder used has a particle size of 2 μm to 10 μm and a purity of ≥99.5%.
4. The method for preparing the surface coating of the tungsten-copper composite material according to claim 3, characterized in that: Step 2 is specifically as follows: add deionized water or ethanol to a container, add Cr powder or Ti powder according to a powder mass concentration of 30 g / L to 50 g / L, use polyvinyl pyrrolidone as a dispersant, and the amount of polyvinyl pyrrolidone relative to Cr powder or Ti powder is 1 g / L to 2 g / L, stir evenly, and use ultrasonic treatment at an ultrasonic frequency of 40 kHz to 60 kHz for 10 min to 15 min to prepare a Cr or Ti suspension; polish the surface in step 1 The tungsten-copper composite material is placed in an electrolytic cell filled with a suspension for electrophoretic deposition, wherein the deposition voltage is 30V-50V; the electrophoresis time is 2min-10min; the suspension temperature is 20℃-25℃; the stirring rate is 200rpm-400rpm; after the deposition is completed, it is dried at 100℃-150℃ for 1 hour, and after it is fully dried, it is kept at 900℃-1000℃ for 3h-5h, and the Cr or Ti bonding layer is HIP treated to complete the preparation of the bonding layer.
5. The method for preparing the surface coating of the tungsten-copper composite material according to claim 1, characterized in that: In step 3, the transition layer is prepared by atmospheric plasma spraying, and the specific process parameters are: wherein the particle size of MoSi2 powder is 15 μm to 45 μm; Purity: ≥99%; flow rate of main gas Ar: 35L / min~45L / min; flow rate of auxiliary gas H2: 5L / min~8L / min; arc power is 25kW~40kW; current: 400A~600A; voltage: 50V~70V; spraying distance: 80mm~120mm; Spraying rate: 4g / min~6g / min; substrate preheating temperature: 200℃~300℃; coating thickness control: single spraying thickness 10μm~20μm, layer by layer to target thickness: 50μm~150μm.
6. The method for preparing the surface coating of the tungsten-copper composite material according to claim 1, characterized in that: Step 4 is specifically as follows: weigh high-purity powders according to the following mass percentages of each component: HfB2 60-80%, SiC 10-30%, La2O3 5-15%, and the powder particle size is 20μm-50μm, put the three powders into a planetary ball mill, use anhydrous ethanol as a solvent, add polyvinyl alcohol equivalent to 0.5%-2% of the total mass of the HfB2-SiC-La2O3 mixed powder as a binder, add silane coupling agent equivalent to 0.1%-1% of the total mass of the HfB2-SiC-La2O3 mixed powder as a dispersant, mix on a planetary ball mill for 8h-12h, and after mixing evenly, prepare spherical HfB2-SiC-La2O3 powder by spray granulation, and directly deposit it on the overcoat by plasma spraying. On the transition layer, the flow rate of the main spraying gas Ar is 35L / min~45L / min; the flow rate of the auxiliary gas H2 is 8L / min~12L / min, the arc power is 35kW~50kW, the current is 400A~600A, the voltage is 50V~70V, the spraying distance is 100mm~150mm, the spraying rate is 15g / min~20g / min; the substrate preheating temperature is 300℃~500℃; the coating thickness control: the single spraying thickness is 10μm~20μm, and it is superimposed layer by layer to the target thickness: 100μm~500μm, and the preparation is completed.
7. The method for preparing the surface coating of the tungsten-copper composite material according to claim 6, characterized in that: In step 4, the particle sizes of the three powders of HfB2, SiC and La2O3 are all 20μm to 50μm; in step 4, the ball-to-material ratio is 2:
1.
8. Surface coating of tungsten-copper composite material, characterized in that: The invention comprises sequentially arranging a tungsten-copper composite material as a bonding layer (2), a transition layer (3) and a heat-insulating and ablation-resistant layer (4) on the surface of a tungsten-copper substrate (1), wherein the surface coating of the tungsten-copper composite material is prepared by the method described in any one of claims 1 to 7.